Rapid progression of left ventricular wall thickness predicts mortality in cardiac light-chain amyloidosis - Kristen, Arnt; Dengler, Jolanta; Schönland, Stefan; Hansen, Alexander E. W.; Hegenbart, Ute; Sack, Falk-Udo; Goldschmidt, Hartmut; Katus, Hugo; Dengler, Thomas (The journal of heart and lung transplantation, 2007)
Background - Cardiac amyloidosis (CA) is the most problematic cause of heart failure because medical treatment strategies are not well tolerated. Due to its high mortality, identification of patients at high risk is crucial for treatment strategies such as heart transplantation prior to chemotherapy for amyloid disease. - Methods - Left ventricular wall thickness (LVT) progression was retrospectively compared with electrocardiographic and echocardiographic parameters for risk prediction in 39 patients with histologically proven cardiac amyloidosis. - Results - Seventeen deaths occurred, equivalent to 1- and 3-year survival rates of 62.1% and 55.0%, respectively. LVT progression in deceased patients was 2.02 ± 0.85 mm/month compared with 0.19 ± 0.03 mm/month in survivors (p < 0.001). Autologous stem-cell transplantation (n = 22, or 54%) reduced LVT progression as compared with not receiving stem cells (0.21 ± 0.04 mm/month vs 1.45 ± 0.57 mm/month, p < 0.005). LVT progression correlated with maximal LVT and absolute LVT increase. Progression of LVT was more rapid in patients with impaired LV ejection fraction (LVEF) than preserved LVEF (2.16 ± 1.04 mm/month vs 0.30 ± 0.13 mm/month, p < 0.001). LVT closely correlated with survival, whereas initial, maximum or absolute increase in LVT did not. Further predictors of survival were LVEF, autologous stem-cell transplantation and low voltage, but not diastolic dysfunction. Multivariate analysis identified LVT progression as the strongest independent parameter for survival. - Conclusions - LVT progression is a powerful risk predictor in light-chain CA, superior to parameters such as LVEF, LVT or a low-voltage pattern. Improved survival by high-dose chemotherapy and stem-cell transplantation is paralleled by a reduction in LVT progression. Repetitive echocardiographic assessment appears indicated in CA patients to identify candidates for heart transplantation in amyloidosis.
Gesehen am 22.01.2022